Pemberdayaan Masyarakat melalui Program â€œKampung InggrisMengajarâ€ di Kampung InggrisKecamatan Pare Kabupaten Kediri - Nurcahyaningtias, Pipit; Askafi, Eka; Baehaki, Imam (Universitas Islam Kadiri, 2024)
Actively mastering English has become a necessity. In its development, English has become a lingua franca and is used as a measuring tool in various types of work. Kampung Inggris in the Pare - Kediri has become an English learning center visited by students from various cities in Indonesia. In fact, the potential of Kampung Inggris is not comparable to the empowerment of local residents, most entrepreneurs are dominated by residents from outside Pare. The local residents' poor English language skills prompted the Forum Kampung Bahasa to initiate the